PELAKSANAAN PENGAWASAN OLEH DINAS KESEHATAN TERHADAP PRODUKSI AIR BERSIH ISI ULANG DI KOTA PEKANBARU - Wandi Rahman Ginting; Sufian Hamim (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2016)
Water is an essential material in life. Water is also a basic need for life; man during his life always need water, especially for drinking water. In the less hygienic drinking water, there is the content of coliform bacteria, which is able to live in the human digestive tract, so that the microbiological analysis of drinking water using the ALT (Angka Lempeng Total) and MPN (Most Probable Number) method is required. Drinking water in the depot is also likely there are contamination of coliform bacteria that is possible due to the lack of perfect care and contamination of contact with human hands contaminated by coliform bacteria. Water quality generally indicates the quality or condition of water associated with a particular activity or necessity. While the quantity concerns the amount of water that humans need in certain activities. Water is an essential material in life, no living thing in this world does not need water. Most of the human body itself consists of water. The average human body contains water as much as 90% of its body weight. Adult body, about 55-60%, body weight consists of water, for children about 65% and for babies about 80%. Clean water is needed in the fulfillment of human needs to do all their activities. So keep in mind how the water is said to be clean in terms of quality and can be used in sufficient quantities in the daily activities of human beings. In terms of quality, there are some requirements that must be met, including physical qualities consisting of odor, color and taste, chemical qualities consisting of pH, hardness, etc. and biological quality where water is free from disease-causing microorganisms. In order for human survival to proceed smoothly, clean water must also be available in sufficient quantities in accordance with human activities at a certain place and a certain period of time.